35th Bled eConference – Digital Restructuring and Human (Re)action: June 26 – 29, 2022, Bled, Slovenia, Conference Proceedings (University of Maribor Press, 2022)
The Bled eConference, organised by the University of Maribor, Faculty of Organizational Sciences, has been shaping electronic interaction since 1988. After 2 years COVID-19 pandemic, when the conference was held online, this year we met again in Bled, Slovenia. The theme of the 35th conference is "Digital Restructuring and Human (re)Action". During the pandemic, we experienced the important role of digital technologies in enabling people and enterprises to interact, collaborate, and find new opportunities and ways to overcome various challenges. The use of digital technologies in these times has accelerated the digital transformation of enterprises and societies. It will be important to leverage this momentum for further implementation and exploitation of digital technologies that will bring positive impacts and solutions for people, enterprises and societies. The need to achieve sustainability goals and sustainable development of society has increased. Digital technologies will continue to play an important role in achieving these goals. The papers in this conference proceedings address digital transformation of enterprises, digital wellness and health solutions, digital ethics challenges, artificial intelligence and data science solutions, new and digital business models, digital consumer behaviour and solutions, including the impact of social media, restructuring of work due to digital technologies, digital education challenges and examples, and solutions for smart sustainable cities.